ANALYSIS OF TOURISTS' ATTITUDE TOWARDS RESPONSIBLE CONSUMPTION IN THE TOURISM SECTOR - Narkūnienė, Ramutė; Šinkūnaitė, Ugnė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the article, the authors analyze tourists' attitude towards responsible consumption in the tourism sector. The problem of responsible consumption is relevant on a national and international scale. The purpose of the research is to analyze tourists' attitude towards responsible consumption in the tourism sector. The tasks of the research are to carry out a theoretical analysis of tourists' attitude towards responsible consumption in the tourism sector and a research of tourists' attitude towards responsible consumption in the tourism sector. During the research, a quantitative survey (questionnaire survey) was conducted. Data collection methods are analysis of scientific literature and sources, document analysis and questionnaire survey. The article reviews tourists’ attitude towards responsible consumption from a theoretical perspective, discusses the benefits of responsible consumption, analyzes tourists' attitude towards responsible consumption in the tourism sector and the tourism institutions attitude towards responsible consumption. It is concluded that most of the respondents try to be responsible consumers during their stay in accommodation establishments. Responsible consumption is mostly motivated by a sense of responsibility, caring for the environment and oneself, and the desire to contribute to positive changes.